A Biochip for Genotyping Polymorphisms Associated with Eye, Hair, Skin Color, AB0 Blood Group, Sex, Y Chromosome Core Haplogroup, and Its Application to Study the Slavic Population - Fesenko, D O; Ivanovsky, I D; Ivanov, P L; Zemskova, E Yu; Agapitova, A S; Polyakov, S A; Fesenko, O E; Filippova, M A; Zasedatelev, A S (Molekuliarnaia biologiia, 2022)
This paper presents a method for genotyping a panel of 60 single nucleotide polymorphisms (SNPs) using single-stage PCR followed by hybridization on a hydrogel biochip. The pool of analyzed polymorphisms consists of 41 SNPs included in the HIrisPlex-S panel, 4 SNPs of the AB0 gene (261G>Del, 297A>G, 657C>T, 681G>A), markers of the AMELX and AMELY genes, and 14 SNP markers of the Y chromosome haplogroups: B (M60), C (M130), D (CTS3946), E (M5388), G (P257), H (M2920), I (U179), J (M304), L (M185), N (M231), O (M175), Q (M1105), R (P224) and T (M272). These genetic data allow one to predict the phenotype of the desired person according to the characteristics of eye, hair, skin color, AB0 blood group, sex, and genogeographic origin in the male line. The setting protocol is simplified as much as possible to facilitate the introduction of the method into practice. The distribution of allele frequencies of the studied polymorphisms, as well as AB0 blood groups among the Slavs (N = 482), originating mainly from central Russia, was established.This paper presents a method for genotyping a panel of 60 single nucleotide polymorphisms (SNPs) using single-stage PCR followed by hybridization on a hydrogel biochip. The pool of analyzed polymorphisms consists of 41 SNPs included in the HIrisPlex-S panel, 4 SNPs of the AB0 gene (261G>Del, 297A>G, 657C>T, 681G>A), markers of the AMELX and AMELY genes, and 14 SNP markers of the Y chromosome haplogroups: B (M60), C (M130), D (CTS3946), E (M5388), G (P257), H (M2920), I (U179), J (M304), L (M185), N (M231), O (M175), Q (M1105), R (P224) and T (M272). These genetic data allow one to predict the phenotype of the desired person according to the characteristics of eye, hair, skin color, AB0 blood group, sex, and genogeographic origin in the male line. The setting protocol is simplified as much as possible to facilitate the introduction of the method into practice. The distribution of allele frequencies of the studied polymorphisms, as well as AB0 blood groups among the Slavs (N = 482), originating mainly from central Russia, was established.